2018
DOI: 10.1016/j.neucom.2018.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Tree Memory Networks for modelling long-term temporal dependencies

Abstract: In the domain of sequence modelling, Recurrent Neural Networks (RNN) have been capable of achieving impressive results in a variety of application areas including visual question answering, part-of-speech tagging and machine translation. However this success in modelling short term dependencies has not successfully transitioned to application areas such as trajectory prediction, which require capturing both short term and long term relationships. In this paper, we propose a Tree Memory Network (TMN) for jointl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…The authors in [1,5,3,2] and our prior works [6,20,21,4] have extensively demonstrated the effectiveness of what are termed "memory modules"…”
Section: Neural Memory Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors in [1,5,3,2] and our prior works [6,20,21,4] have extensively demonstrated the effectiveness of what are termed "memory modules"…”
Section: Neural Memory Networkmentioning
confidence: 99%
“…These dependencies are missed by models such as LSTMs and Gated Recurrent Units (GRUs) as they consider dependencies only within a given input sequence. Due to this ability external memory modules have gained traction in numerous domains, including language modelling [1], visual question answering [3], trajectory prediction [6,20], object tracking [5], and saliency modelling [4].…”
Section: Neural Memory Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The generative model then randomly chooses among the seeds to generate new sentences using an attention-based bidirectional long short-term memory (Bi-LSTM) model (Fernando et al, 2018;Wang et al, 2019). This approach dynamically adapts to extract and identify unseen instances.…”
Section: Introductionmentioning
confidence: 99%
“…To train the generative model, the method takes as input a collection of domain-specific entities and domain-general words along with their corresponding frequencies (referred to as sample seeds). The generative model then randomly chooses among the seeds to generate new sentences using an attention-based bidirectional long short-term memory (Bi-LSTM) model (Fernando et al, 2018;Wang et al, 2019). The process of generating sentences based on a unigram language model is iteratively repeated until the algorithm converges (Guo et al, 2017;Qiu et al, 2018;Quijano-Sánchez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%